Redeemability of Mortgage Hypotheca: Exercise and Deferral from Bangladesh Perspective - Khurshid, Md Khurshid Alam; Raushan, Raushan Ara (Dhaka University Law Journal, 2026)
The right of redemption is the most significant legal right that protects the interest of a mortgagor, in addition to other rights shaped by the mortgage deed, among the numerous statutory privileges that any mortgagor can assert. The discussion on this right pertains to redemption following the completion of the equity of redemption, its exercise by the parties and the operation of the law, procedural aspects of redemption, such as subrogation, suits, limitation, and lis pendens, certain collateral advantages after redemption, deferral of redemption, and numerous innuendoes with current case laws. In fast-paced environments, the right of redemption in mortgages is examined to see whether it is equitable or statutory in substantive laws and numerous court decisions. It must be noted that the redeemability of the mortgage hypotheca ascends when ownership of the property is transferred in a qualified form. This article emphasizes the right of redemption, its exercise, deferral, sporadic factors, implications, and aftermath in the context of Bangladesh, as supported by legal precedent. Dhaka University Law Journal, 2025, 36 (2), 01-21